Willingness to perform environmentally friendly practices in rural areas: evidence from environmental regulation in agriculture - Zhang, Weikun; Liang, Sicheng; Wu, Wanying; Zhuang, Haijie; He, Qinqing (Frontiers in Environmental Science, 2025)
BackgroundEnvironmental problems arising from agriculture and rural living have drawn increasing scholarly attention worldwide. The transition from traditional, resource-intensive farming and rural practices to more ecologically responsible modes of production and household behaviors has become a critical challenge.MethodsPromoting the transformation of farmers' green production methods and lifestyles is of great significance to the greening of China's rural areas, which determines the importance of analyzing the underlying logic behind farmers' willingness to perform environmentally friendly practices (FWPEPs). Against this backdrop, an empirical study was carried out using the probit model, based on the analysis framework of digitization and farmers' data from the China Land Economic Survey from 2021 to 2022.ResultsThe findings revealed that farmers' willingness to perform environmentally friendly practices can be attributed to both constrained environmental regulation–through mandatory laws and regulations–and incentive-based environmental regulation involving economic subsidies and other incentive measures. The positive effect of environmental regulation on FWPEPs varies according to gender and education level.ConclusionsDigitization plays an important regulatory role by enhancing farmers' environmental awareness and rule perception and encouraging them to adopt more environmentally friendly production methods and lifestyles. These insights enable policymakers to design targeted, environmentally friendly, and sustainable mitigation strategies by synergizing regulatory precision with digital empowerment.